Social media influence on self-image and motivation for cosmetic and plastic surgery in Kuwait - Alfares, Mohammed A A A (My University, 2024)
This thesis explores the influence of social media on body image perceptions and the motivations for cosmetic and plastic surgery (CPS) among individuals in Kuwait. With the increasing presence of Western beauty standards on social media platforms such as Instagram and Snapchat, this research investigates how these standards affect body dissatisfaction and intentions to undergo CPS in a society that balances traditional values with modern beauty ideals. The study uses the Theory of Planned Behavior (TPB) to analyze the role of attitudes, subjective norms, and perceived behavioral control in shaping CPS intentions within the Kuwaiti context. Other key variables included social media use, exposure to Western beauty standards, body image perceptions (both positive and negative), intentions to undergo CPS, beliefs regarding CPS, concerns and risks involved in CPS, and perceived subjective norms of CPS. A quantitative approach was employed, with data collected through an online survey (n=300). The sample was composed of 128 men, 137 women, and 23 who preferred not to identify. Descriptive statistics were calculated, including percentages, means, and standard deviations. Correlation and regression analyses were conducted to test the hypotheses and answer the research questions. The results show that frequent social media use was correlated with greater motivation for CPS. This was confirmed by significant correlations between social media use and attitudes (r = .172, p < .01), intentions (r = .195, p < .01), and beliefs regarding CPS (r = .211, p < .01). Exposure to Western beauty standards influences negative body image perceptions (r = .636, p < .01). Similarly, exposure to these beauty standards is positively correlated with attitudes toward CPS and intentions to undergo CPS, which was supported by the data (r = .178, p < .01 and r = .287, p < .01, respectively). Results also show that subjective norms on CPS intentions, that is, support from friends and family significantly increased motivation to undergo CPS (β = .293, p < .001). In testing the research questions results show significant differences in positive body image perceptions between those who had undergone CPS and those who had not. However, it was the subjective norms, especially social acceptance, and support from close circles, that significantly predicted intentions to undergo CPS (β = .293, p < .001). Lastly, identified beliefs about CPS and social motivations as strong predictors of CPS intentions, accounting for 40% of the variance in intention (R² = .403). This study demonstrates the significant role of social media in shaping body image and influencing cosmetic surgery trends in Kuwait. These findings suggest that culturally sensitive interventions are needed to promote healthier body image perceptions and reduce the negative psychological impacts of social media-driven beauty ideals.
Keywords: Social media; Self-image; Cosmetic and plastic surgery; Motivation; Theory of planned behavior